Cobitis feroniae, a new spined loach from southern Latium, Italy (Teleostei: Cobitidae) - Novaga, Riccardo; Bellucci, Davide; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2024)
Cobitis feroniae, new species, is described from central Italy. It is distinguished from C. zanandreai, its putatively closest relative, by having several, small, black dots below Z4; minute, black spot at the upper caudal peduncle, and the pigmentation in Z2 separated from pigmentation in Z1 anterior to the dorsal-fin origin. It is further distinguished from C. zanandreai by having 13 diagnostic nucleotide substitutions in the mtDNA COI barcode region, and a K2P nearest–neighbour distance of 2.9%.